TRANSLATION AS A MEANS OF LEARNING AND SELF-LEARNING IN STUDYING ARABIC AS A FOREIGN LANGUAGE - Gross, Annegret M. (European Scientific Journal, ESJ, 2014)
Using translation in foreign language teaching has been a rather controversial topic in recent times. While translation was generally accepted as a regular teaching method up to the 18th century, the trend slowly reversed to a merely monolingual approach during the 19th century. In the last two decades, however, the bilingual approach is again given more attention and possibilities of combination are increasingly being discussed. This paper aims at demonstrating how integrating translation into L2 learning by the example of Arabic can help learners to better learn the language, master its particularities and grasp a better understanding of the language right from the beginning, especially when it comes to syntax, grammar, and phraseology. For autonomous learning, relevant motivation theories in teaching and learning are highlighted and a strategy in order to benefit from translation in self-learning is being suggested.